α-Amino Acid Synthesis by 1,3-Nitrogen Migration: An Update - Yin, Kuan; Meggers, Eric (Synthesis, 2024)
An improved practical and efficient procedure for the synthesis of non-racemic unnatural α-amino acids through a stereocontrolled rearrangement is reported. Carboxylic acids are converted into azanyl esters RCO2NHBoc followed by an iron-catalyzed 1,3-nitrogen migration to provide non-racemic α-amino acids in an asymmetric (α-monosubstituted α-amino acids) or enantioconvergent fashion (α,α-disubstituted α-amino acids). Under optimized conditions using a fluorinated chiral iron catalyst and 2,2,6,6-tetramethylpiperidine as the base in a solvent mixture of 1,2-dichlorobenzene and CHCl3, enantioselectivities of up to 98% ee were obtained. Such high ee values are important for practical purposes, allowing the direct use of many of the obtained N-Boc-protected α-amino acids for subsequent applications.
Keywords: α-amino acids; asymmetric catalysis; iron; C(sp3)−H amination; rearrangements